Three-Dimensional Package Design for Electro-Absorption Modulation Laser Array - Zhike Zhang; Yu Liu; Jiasheng Wang; Jinhua Bai; Haiqing Yuan; Xin Wang; Jianguo Liu; Ninghua Zhu (IEEE Photonics Journal)
We report a new 3-D package design technique in this paper. Based on this technique, a 3-D RF impedance matching circuit used in the packaging of electroabsorption modulation laser (EML) array is achieved, which has the characteristics of low electrical crosstalk and small size. The 3-D package design technique overcomes the limitation of conventional 2-D design technique in which many bonding wires have to be employed. The measurement results demonstrate that the 3-D impedance matching circuit has a transmission bandwidth of 25 GHz and the reflection is suppressed below −10 dB in a wide frequency range. Compared with NTT's schemes, the 3-D impedance matching circuit and the wires in our scheme have a lower electrical crosstalk. A ten-channel EML module is fabricated, employing the above technique, and demonstrated. The module has good frequency characteristics over a bandwidth of 10 GHz. To our knowledge, this is the first time that such a 3-D impedance matching circuit has been reported publicly.